PENGARUH MEDIA SOSIAL, EVENT PARIWISATA, DAN FASILITAS PELAYANAN TERHADAP MINAT BERKUNJUNG ULANG DI SANDBOARDING GUMUK PASIR PARANGKUSUMO - Zulanda Pratiwi; Adhi Prakosa (Jurnal Fokus Manajemen Bisnis, 2021)
This study aims to determine the effect of social media, tourism events, and service facilities on revisiting interest in Gumuk Pasir Parangkusumo Sandboarding. The research was conducted on visitors to the Parangkusumo Gumuk Pasir Sandboarding. This research is a quantitative research. The sample used in this study amounted to 100 respondents. This study used purposive sampling technique and data analysis with multiple linear regression. Hypothesis testing using the T test and F test with the help of the application program SPSS version 16.0. The results of the multiple linear regression indicate that social media has a positive and significant effect on revisiting interest. Tourism events have a positive and significant effect on revisiting interest. Service facilities have a positive and significant effect on revisiting interest. Based on the results of the F test, it shows that social media, tourism events, and service facilities simultaneously have a significant effect on revisiting interest.